2011
DOI: 10.4081/reumatismo.2008.1s.70
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia syndrome: preventive, social and economic aspects

Abstract: Fibromyalgia (FM) is a central pain syndrome that is characterized, in part, by specific tender points (TPs) in the musculoskeletal system which are exceptionally sensitive to pressure. Pain, specifically characterized as hyperalgesia and allodynia, is the cardinal symptom of FM; however, most patients also experience additional symptoms such as debilitating fatigue, disrupted or nonrestorative sleep, functional bowel disturbances, and a variety of neuropsychiatric problems, including cognitive dysfunction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…Various questionnaires were used to investigate the description of pain, healthcare use before and after enrolment, and the willingness to pay for therapy. A previous study by the Italian Fibromyalgia Network showed that a high degree of disability and the number of pathologies associated with FM could significantly increase the direct and indirect costs of FMrelated pain management, whereas an early diagnosis reduced the use of economic resources for drugs, medical appointments and diagnostic investigations (18).…”
Section: N Costs Of Pain In Osteoarthritismentioning
confidence: 99%
“…Various questionnaires were used to investigate the description of pain, healthcare use before and after enrolment, and the willingness to pay for therapy. A previous study by the Italian Fibromyalgia Network showed that a high degree of disability and the number of pathologies associated with FM could significantly increase the direct and indirect costs of FMrelated pain management, whereas an early diagnosis reduced the use of economic resources for drugs, medical appointments and diagnostic investigations (18).…”
Section: N Costs Of Pain In Osteoarthritismentioning
confidence: 99%
“…Despite substantial progress achieved with the development of new antidepressants in recent decades, the therapy is not completely effective, and approximately 40% of patients do not respond to treatment (Altomonte et al, 2008). The characterization of the antidepressantlike effect of natural substances is justified by the need to find new compounds that have greater clinical efficacy and fewer adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Asociarse entre sí les ayuda a combatir la soledad que sufren. En este sentido, tanto Altomonte 48 como Vázquez 49 explican que la participación voluntaria en asociaciones es un factor de apoyo para las pacientes con FM, haciéndolas sentirse protegidas, comprendidas y mejorando la forma en que enfrentan su enfermedad. Como se ha comentado, son estas asociaciones, instituciones sólidas para reducir la vulnerabilidad social que sufren estas pacientes en parte debido a su escasa integración laboral y a la falta de un círculo de apoyo.…”
Section: Asociacionismounclassified
“…Como asociaciones de pacientes, ganan agencia, capacidad de exigir más atención del poder ejecutivo e influencia en las decisiones políticas sobre la salud y, de paso, conducen al sistema a la apertura institucional. Para Altomonte 48,49 , unirse voluntariamente a una asociación, es además una forma de responsabilidad social que estas usuarias contraen con el fin de promover el conocimiento que tiene la ciudadanía sobre la enfermedad. Según Chesler y Pérez 52 , en este caso, se debe proteger la posibilidad de que las personas se cuiden unas a otras y promover la infraestructura que lo permita para que el cuidado no sea enteramente un asunto ni individual, ni del Estado y su infraestructura.…”
Section: Asociacionismounclassified